A Monte Carlo study of the anisotropy effects on the spin state evolution in ultrathin helimagnetnanorings. (14th January 2015) - Tian, Guo; Song, Xiao; Li, Peilian; Qin, Minghui; Zeng, Min; Gao, Xingsen; Liu, Junming
Abstract: In this work, the magnetic states in ultrathin helimagnet nanorings were investigated using a Monte Carlo simulation, based on a Heisenberg model involving the short-range exchange coupling, Dzyaloshinsky-Moriya interaction, long-range dipolar interaction, and perpendicular anisotropy. The competition of these interactions leads to the stabilization of various spin states at zero magnetic field, e.g. necklace-like skyrmion chain state, twin-vortex with two coaxial vortices carrying two opposite charities, depending on geometric and anisotropy parameters. A vortex–to–skyrmion-chain transformation triggered by varying the anisotropy was also revealed. Nanorings with different anisotropy also exhibit completely different magnetization reversal hysteresis loop against magnetic field. Finally, a spin state diagram based on anisotropy and magnetic field was constructed. The present work suggests a novel opportunity to manipulate the spin configurations in nanomagnets, which may find applications in high-density data storage or spintronic devices.